Hard And Soft Tissue Changes Following Two Modes Of Retention Management After Twin Block Therapy: A Retrospective Cephalometric Study - Maurtgi, Moustafa Said Moustafa Said (2018)
A retrospective cephalometric study was conducted in the Advanced Medical & Dental Institute (AMDI), Universiti Sains Malaysia (USM), to assess the soft and hard tissues changes that occur in two sets of patients receiving two different relapse management after Twin block therapy. The radiographic records consisted of Malay ethnicity patients age ranged between 10 and 15 years. Patients were diagnosed as Class II Division 1 malocclusion with overjet of 5 mm or greater or Class II skeletal pattern of ANB angle of 5o or greater and were treated with the Twin block appliance. The records of 26 patients were found and were divided into two groups. Group (A) is those radiographs from subjects who received fixed orthodontic appliance immediately after the Twin block therapy and group (B) is those radiographs from subjects who received fixed orthodontic appliance after 3 months retention period after Twin block therapy. Lateral cephalometric radiographs from the database were grouped into, (T1): before Twin block therapy, (T2): after Twin block therapy completion, and (T3): after 6 months of fixed appliance placement. Several cephalometric analyses were used including Holdaway, Burstone, Pancherz, and Steiner to assess soft tissue changes and hard tissue changes weather that be skeletal, dental, or dento-alveolar. Mann-Whitney test to compare pre-treatment (T1) measurements of groups A and B patients. Wilcoxon signed-rank test was used to detect changes occurring through time within the groups. Changes between group A and B in (T2) and (T3) were compared using Mann-Whitney test.